Dynamic Capabilities as a Determinant of Small Enterprise Development: The Case Study of Poland - Renata LISOWSKA (Communications of International Proceedings, 2022)
Dynamic capabilities are an enterprise's predispositions which constitute its potential allowing for developing, integrating and reconfiguring key competences in order to adapt to changes taking place in the environment. These capabilities should make it possible to achieve the expected level of effectiveness, assessed both in the market dimension (from the perspective of value and benefits for the client) and in the economic dimension (from the perspective of value and benefits for the enterprise) by influencing the process of building relations with the environment as well as the business processes implemented within the company. The aim of the article is to examine the essence of dynamic capabilities in the context of enterprise development and to present the results of the research on the level of dynamic capabilities of Polish small enterprises.The study was conducted in October and November 2019 using the CATI technique among owners/co-owners of micro and small enterprises operating in Poland. The size of the sample was 400. The results of the research conducted indicate the impact of dynamic capabilities on enterprise  development, i.e. the higher the level of dynamic capabilities, the greater the development orientation. The following conclusions have been additionally formulated: (i) there is a relationship between the level of dynamic capabilities and the age of the enterprise, (ii) there is no relationship between the level of dynamic capabilities and the size of the enterprise.
Keywords: dynamic capabilities; enterprise development; small enterprise; development determinants.